48 million configurations and counting: platform numbers and their capitalization. Issue 1 (2nd January 2018) - Mackenzie, Adrian
ABSTRACT: Platforms are important actors in contemporary cultural economic processes. They include social network sites, online content management systems, streaming media platforms, mobile communication infrastructures, supply chain logistics solutions, and cryptocurrencies. Analysis of platforms and their capitalization should take into account the ways they structure social practice as assets and the constitutive opacity of platforms as configured realities. It explores capitalization by focusing on the problems of counting people and things on platforms. Via a case study of the software repository platform [Github.com] (https://github.com ), it analyzes how 'platform numbers' participate in capitalization. It describes attempts to enumerate the elements of the platform by counting, mapping or listing them. The paper shows how attempts to enumerate people and things encounter forms of association, duplication, combination, imitation and configuration that are crucial to the ensemble but remain refractory to capitalization. It proposes configurative enumeration of the platform numbers as a way of conceptualizing these un-enacted excesses. In a configurative enumeration, the composition, the rhythms of imitation, variation and commutation, and constant relating, repairing and adjusting of configurations crucial to the ongoing formation of platforms come into view. Configurative enumerations engage the inventive realities of platformization, realities that precede and sometimes overflow their capitalization.